Iced photochemical reduction to synthesize atomically dispersed metals by suppressing nanocrystal growth - Hehe Wei (Nature Portfolio, 2017)
Photochemical synthesis is a popular approach to fabricate metallic nanoparticles, however stabilizing individually-dispersed atoms by this method remains challenging. Here, the authors freeze their precursor solution prior to UV irradiation to obtain atomically-dispersed platinum catalysts with high electrocatalytic performance.